Konsep Pendidikan Dengan Kurikulum Terpadu (Alam, Akhlak, Nasional) Untuk Siswa Berkebutuhan Khusus Pada Sekolah Citra Alam - Karimah, Umi; Shilvy Anggelia; Diki Walhadi; Adinda Zahra Sukmahati; Syafirah Fiqri; Taufik Muhtarom (CV. Ulil Albab Corp, 2025)
This research aims to determine the concept of education in natural schools in one of the regions, namely Yogyakarta, by implementing an integrated curriculum (Akhlak, Nature, National) for children with special needs. The moral curriculum implemented is strong morals in line with the vision and mission, positive values ​​and supported by strong personal potential (interests and talents, creative and innovative, traces of work, work studio, and portfolio). The natural curriculum applied at Citra Alam School with an environmentally friendly lifestyle is a school garden, independent energy and an independent kitchen. Each element of the natural climate has activity from these indicators, such as local food, variety of plants, variety of planting, energy saving, renewable energy innovation, food processing, waste sorting, natural learning media and mandatory use of drinking bottles and places to eat. The national curriculum is in accordance with government regulations, namely the Merdeka curriculum which focuses on students' skills and personalities. Through these three curricula, Citra Alam School students can learn flexibly and especially children with special needs can explore the natural surroundings without any restrictions. Children with special needs will of course receive special guidance with psychological assistance.